Tlingit Verb Dictionary (Part 1: English-Tlingit; Part 2: Tlingit-English) - Naish, Constance M.; Story, Gillian L.; Youngkin, Constance V. (University of Alaska, Alaska Native Language Center, 1973)
https://www.sil.org/resources/archives/2515